(untitled) (International Journal of Engineering and Computer Science, 2016)
Privacy of data is one of the major issues in every network. The network may be wired or wireless and the network may be ad-hoc, pear to pear or distributed network privacy of data is an important factor in each case. In each case in a distributed or shared network all people connected in a network work with the protocol. But there is no guarantee of security threat and data lost or stolen. So precautions needed in each case to maintain the network and to maintain the private data. An Ad-hoc network is a Local Area Network (LAN) which is built spontaneously as devices connect. Instead of depending upon a base station to manage the dataflow, each node in a network forward data packets to each other. As all most all nodes are responsible for data flow, so the probable data lost or stolen of information cannot be neglected. In order overcome these problems in data mining there should be some proper protocols as well as some special precautions should be taken. There are many experiments and developments already done in this aspect to secure data as well as to secure the network. This paper provides a review of various security challenges that are already taken for protection of privileged information in various peer to peer network, shared or distributed network. We have also proposed a technique for privacy preservation of privileged information in case of an Ad-hoc network. This technique may provide a better security for the privileged information in an Ad-hoc network.